Preparation and characterization of poly(hydroxybutyrate-co-hydroxyvalerate)/clay nanocomposites - Mohd Anuar, Mohd Firdaus (2012)
In this study, natural clay (Na-MMT) and synthetic layered double hydroxide (LDH) were modified to produce organo-modified clay. LDH was prepared via co-precipitation method by adding dropwise a solution of NaOH (1M) into a solution of Mg(NO3)2·6H2O and Al(NO3)3·9H2O. Both Na-MMT and LDH were modified via ion exchange technique using octadecylamine (ODA) and sodium stearate respectively to perform organo-modified clays. The modification was carried out by stirring the clay in an aqueous solution of a mixture of Na-MMT and ODA, and LDH and sodium stearate. The modified clays were then used in preparation of poly(hydroxybutyrate-co-hydroxyvalerate), PHBV nanocomposites. The intercalation of the modifier in the clays layer were characterized by X-ray Diffraction (XRD) Analysis and Fourier Transform Infrared (FTIR) Spectroscopy. PHBV/clay nanocomposites were prepared via solution casting technique. The clays were added into chloroform solution of PHBV based on a fixed amount of clay loading. The amount of clays added were 0.25, 0.5, and 1.0 wt% for all type of clays. For further dispersion of clay, the mixture of PHBV/clay solution was sonicated for 30 min. The viscous solutions were casted in a glass petri dish and dried in the solvent atmosphere to obtain the nanocomposite films. The effect of clay loading on PHBV/clay nanocomposites were characterized by means of mechanical, thermal and morphology properties. The addition of natural and modified clays was found not to increase the tensile strength property of the nanocomposites. However, the elongation at break property was found to increase for all anocomposites. At 0.5 wt% of clay loading of ODA-MMT, the maximum elongation at break was achieved. This result is in accordance with Scanning Electron Microscopy (SEM) analysis which shows the stretching images at 0.5 wt% of clay loading for all nanocomposites. The thermal stability of PHBV/clay nanocomposites was found to increase with the increase of clay loading. Transmission Electron Microscopy (TEM) images showed that exfoliated and intercalated type of nanocomposites was successfully prepared with the incorporation of 1.0 wt% of modified clays loading.